Numerical Simulation of Temperature Distribution in the Gas Turbine Blade - Dariusz Jakubek (Communications - Scientific letters of the University of Zilina, 2021)
This paper concentrates on temperature distribution in the gas turbine blade equipped by the cooling holes system on transient heat transfer. The present study requires the specification of internal and external boundary conditions. The calculations had been done using both Crank-Nicolson algorithm, explicit and implicit methods, in which different heat transfer coefficients on internal cooling surfaces of the holes were applied. The value of coefficients has a direct and crucial impact on the final result. The heat transfer coefficient of cooling the working surface of the of heat pipes was 1600 W/(m2K). It was found that there were no significant differences of temperature distribution in comparison of results from explicit method in the Ansys analysis, Crank-Nicolson algorithm and implicit method in Matlab. The simulation is based on Finite Element Method, which uses the Crank Nicolson algorithm.